2008
DOI: 10.1371/journal.pntd.0000341
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Trachoma Infection and Disease in a Gambian Cohort with Frequent Follow-Up

Abstract: BackgroundThe natural history of ocular Chlamydia trachomatis infections in endemic communities has not been well characterised and is an important determinant of the effectiveness of different mass treatment strategies to prevent blindness due to trachoma.Methodology/Principal FindingsA multistate hidden Markov model was fitted to data on infection and active disease from 256 untreated villagers in The Gambia who were examined every 2 weeks over a 6-month period. Parameters defining the natural history of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 40 publications
(51 reference statements)
6
83
0
1
Order By: Relevance
“…The disease disproportionately affects individuals living in rural and resource-poor settings, and children are the primary carriers of ocular C. trachomatis infection and active disease [3]. We and others have previously shown that clinical disease persists longer than infection in children such that in any prevalence survey, a significant proportion of children will have active trachoma without demonstrable signs of C. trachomatis infection [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…The disease disproportionately affects individuals living in rural and resource-poor settings, and children are the primary carriers of ocular C. trachomatis infection and active disease [3]. We and others have previously shown that clinical disease persists longer than infection in children such that in any prevalence survey, a significant proportion of children will have active trachoma without demonstrable signs of C. trachomatis infection [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…La enfermedad comienza en los niños, principalmente en aquéllos entre 2 y 5 años de edad, en los cuales tiene mayor duración (22)(23)(24), como lo vemos en los casos demostrados, 61% de los cuales eran menores de 15 años. Ellos son la fuente principal de la bacteria; la transmiten a los otros niños y a sus madres (25), principalmente, a través del contacto estrecho, como compartir camas y juegos, que permiten entrar en contacto con las secreciones oculares, o por el intercambio de utensilios contaminados o fómites, como las toallas (1-4,17,22-24).…”
Section: Discussionunclassified
“…Previously, scarring complications were often ascribed to adaptive immune responses, since adults have consistently lower bacterial loads than those of children and experience short duration of infection, presumably as a result of acquired immune responses. [7,18,19]…”
Section: Etiology and Immunopathology Of Clinical Signsmentioning
confidence: 99%